The correlational effects of self-efficacy and supervisor support towards employees' motivation to learn in Petronas Cari Gali Sdn. Bhd. Terengganu / Mazni Abdullah - Abdullah, Mazni (2013)
This research was conducted to study the correlational effects of self-efficacy and supervisor support towards employees' motivation to learn. This study was conducted in PETRONAS Carigali Sdn. Bhd. The questionnaires were distributed to the staffs of Supply Chain Management Department of this organization to study the effects of the two independent variables with motivation to learn. The researcher conducted this study because there is lack of motivation to learn among the staffs of this organization. This study was significant towards the organization, employees, supervisors and readers of this research. In this research, the researcher explained on the theories of the self-efficacy theory, organizational support theory and four-drive theory that contributed to this research. The methodology for this research was explained by the researcher. The researcher used correlational research design, the sample frame was staffs PETRONAS Carigali Sdn. Bhd., the population was both male and female employees, the sampling technique was stratified random sampling while the sample size used was about 70 employees. The researcher used SPSS version to analyze the data. From the findings and analysis, two hypothesis were accepted while three hypothesis were rejected. The researcher recommended some solutions to solve the problem of lack of motivation to learn among the staffs of PETRONAS Carigali Sdn. Bhd.